Metformin Abrogates Age-Associated Ovarian Fibrosis - McCloskey, Curtis W; Cook, David P; Kelly, Brendan S; Azzi, Feryel; Allen, Christian H; Forsyth, Amanda; Upham, Jeremy; Rayner, Katey J; Gray, Douglas A; Boyd, Robert W; Murugkar, Sangeeta; Lo, Bryan; et al. (Clinical cancer research, 2020)
The ovarian cancer risk factors of age and ovulation are curious because ovarian cancer incidence increases in postmenopausal women, long after ovulations have ceased. To determine how age and ovulation underlie ovarian cancer risk, we assessed the effects of these risk factors on the ovarian microenvironment. Aged C57/lcrfa mice (0-33 months old) were generated to assess the aged ovarian microenvironment. To expand our findings into human aging, we assembled a cohort of normal human ovaries ( = 18, 21-71 years old). To validate our findings, an independent cohort of normal human ovaries was assembled ( = 9, 41-82 years old). We first validated the presence of age-associated murine ovarian fibrosis. Using interdisciplinary methodologies, we provide novel evidence that ovarian fibrosis also develops in human postmenopausal ovaries across two independent cohorts ( = 27). Fibrotic ovaries have an increased CD206 :CD68 cell ratio, CD8 T-cell infiltration, and profibrotic DPP4 αSMA fibroblasts. Metformin use was associated with attenuated CD8 T-cell infiltration and reduced CD206 :CD68 cell ratio. These data support a novel hypothesis that unifies the primary nonhereditary ovarian cancer risk factors through the development of ovarian fibrosis and the formation of a premetastatic niche, and suggests a potential use for metformin in ovarian cancer prophylaxis. .